Aerogami: Composite origami structures as active aerodynamic Ccontrol. (1st March 2020) - Cozmei, Mircea; Hasseler, Tristan; Kinyon, Everett; Wallace, Ryan; Deleo, Antonio Alessandro; Salviato, Marco
Abstract: This study explores the use of origami composite structures as active aerodynamic control surfaces. Towards this goal, two origami concepts were designed leveraging a combination of analytical and finite element modeling, and computational fluid dynamics simulations. Wind tunnel tests were performed at different dynamic pressures in conjunction with two different active control laws to test the capability of obtaining desired drag values. The experiments revealed excellent structural rigidity and folding characteristics under aerodynamic loading. These results are in very good agreement with one-way Fluid Structure Interaction (FSI) simulations, which show the potential of using high-fidelity modeling for the design and optimization of these structures. Future work will focus on developing advanced origami designs that allow for more deterministic folding as well as improved weight, stiffness, and fatigue characteristics in the use of materials.